Scientific and Legal Aspect for Conducting of Operational Measures to Counter Threats of Terrorist Acts upon Their Commission as a Challenge to the Social Community - Юрчишин, Василь Миколайович; Юрчишин В. М.; Юрчишин, Василий Николаевич; Yurchyshyn, Vasyl M.; Налуцишин, Віктор Володимирович; Налуцишин, В. В.; Налуцишин, Виктор Владимирович; Nalutsyshyn, Viktor V.; Черепущак, Василь Васильович; Черепущак, В. В.; Черепущак, Василий Васильевич; Cherepushchak, Vasyl V. (ASERS Publishing, 2019)
Terrorist threat act may lie not only in potential civilian casualties, but also in the investigation of acts that could in the long run lead to the implementation of terrorist intentions. The relevance of the study is determined by the fact that the possibility of preventing a terrorist act should be in the interdepartmental jurisdiction of law enforcement agencies not only as a task of emergency response, but also as a task of direct monitoring. The novelty of the study is determined by the fact that the authors consider the aspect of the formation of countermeasures against a terrorist act on the basis of liquidating the foundation of its social response. The very process of preventing a terrorist act predominantly affects only measures to destroy terrorists and reduce the number of potential victims. The paper demonstrates that in addition to this postulate, it is worth considering the need for an additional reduction in social resonance, which acts as an incentive. Formation of counteraction by law enforcement agencies allows to reduce the significance of the terrorist impact on society. The practical significance of the study is determined by the fact that each of the participants in countering the terrorist act is also capable of operative activities, which can also additionally level the structure for implementing the provisions of anti-terrorism legislation.

Терористична загроза може полягати не тільки в потенційних жертвах серед цивільного населення, а й у розслідуванні дій, які в довгостроковій перспективі можуть призвести до реалізації терористичних намірів. Актуальність дослідження визначається тим, що можливість попередження терористичного акту має бути у міжвідомчому віданні правоохоронних органів не лише як завдання реагування на надзвичайні ситуації, а й як завдання безпосереднього моніторингу. Новизна дослідження визначається тим, що автори розглядають аспект формування протидії терористичного акту на основі ліквідації фундаменту його соціального реагування. Сам процес попередження терористичного акту переважно стосується лише заходів щодо знищення терористів та зменшення кількості потенційних жертв. У роботі показано, що окрім цього постулату, варто розглянути необхідність додаткового зниження соціального резонансу, який виступає як стимул. Формування протидії з боку правоохоронних органів дозволяє знизити значущість терористичного впливу на суспільство. Практична значущість дослідження визначається тим, що кожен з учасників протидії терористичного акту також здатний до оперативної діяльності, що також може додатково нівелювати структуру реалізації положень антитерористичного законодавства.
Nalutsyshyn V. V. Scientific and legal aspect for conducting of operational measures to counter threats of terrorist acts upon their commission as a challenge to the social community / V. V. Nalutsyshyn, V. M. Yurchyshyn, V. V. Cherepushchak // Journal of Advanced Research in Law and Economics. - Vol. 10. – Iss. 7. - ASERS Publishing, 2019. – P. 2060-2069.
Keywords: terrorism; operative actions; challenge; social response; response; тероризм; оперативні дії; виклик; соціальна реакція; відповідь; Research Subject Categories::LAW/JURISPRUDENCE